Arabako herri izenen azentueraz / On the accentuation of Basque place names in Álava - Garazi de Olano Martinitz-Xil; Gorka Elordieta (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2018)
This paper analyzes the stress patterns of town and village names of the province of Araba (Basque Country, Spain). There are many names that are accentuated closer to the beginning of the word than to the end of the word (Gardélegi, Etxábarri, Arrízala, Olábezar, Gújuli, Róitegi, etc.). Other names, however, show word stress on the penultimate syllable: Aretxabaléta, Egiléta, Maturána, Urtupíña, Arenáza, Zubillága, Elorriága, Larrinóa, etc. The location of word stress towards the left edge does not coincide with the most frequent location of word stress in Spanish, that is, the penultimate syllable. Our analysis is that word stress is assigned to the last syllable of the root, in words of Basque origin. Thus, in place names with the structure root + affix(es) stress surfaces on the last syllable of the root, and in place names with compound word structure (i.e., root + root (+ affix)) stress surfaces on the last syllable of the first root. In words of Romance origin stress surfaces on the penultimate syllable.